Non _Equivalence at Word Level (Journal of Humanitarian and Applied Sciences, 2023)
Each translation process has one or several specific goals, but the primary and main objective of translation is its work as a link between people of different tongues and cultures. In this sense, translation is not an easy task as many students think. To start a translation process, students often do not pay much attention to the word which is considered the smallest unit of translation, how to translate it, and how to find a proper language equivalent to be used in the target language and what is the strategy used to translate it to make the context and the meaning more clearer.This study highlights the problem of equivalence at word level facedencountered by fifth and sixth semester students at English language department / Faculty of Education Qasser Ben Gashir Tripoli University, when they translate from Arabic to English. Therefore , strategies professional translators use to overcome such problems will be mentioned .
Keywords: Non-equivalence; Word Level; Translation